Mobile Technologies as a Health Care Tool - Arslan, Pelin (PoliMI SpringerBriefs, 2016)
This book presents a state-of-the-art overview of the available and emerging mobile technologies and explores how these technologies can serve as support tools in enhancing user participation in health care and promoting well-being in the daily lives of individuals, thereby reducing the burden of chronic disease on the health care system. The analysis is supported by presentation of a variety of case studies on the ways in which mobile technologies can be used to increase connectivity with health care providers and relevant others in order to promote healthy lifestyles and improve service provision. Detailed information is also provided on a sample project in which a set of tools has been used by teens at risk of obesity to record their sociopsychological environment and everyday health routines. Specifically, it is evaluated whether video diaries, created using a mobile platform and shared in real time via a social network, assist subjects in confronting obesity as a chronic disease. The book will be of interest to all who wish to understand the impressive potential of mobile health or to conduct research in the field.